THE ESSENTIAL ROLE OF DIAGNOSTIC AND TREATMENT METHODS FOR PATIENTS WITH TEMPOROMANDIBULAR JOINT PAIN DYSFUNCTION SYNDROME (World Bulletin of Public Health, 2022)
For a long time, the occurrence of pain dysfunction syndrome has been associated with bite anomalies and deformities, dentition integrity disorders and changes in occlusal height. At the same time patients with prominent dentoalveolar anomalies without temporomandibular joint disturbances as well as patients with pain dysfunction syndrome without occlusal-articular pathology are often encountered in clinical practice.
Keywords: temporomandibular; syndrome; pain